Microfluidic paper-based biomolecule preconcentrator based on ion concentration polarization. Issue 12 (20th May 2016) - Han, Sung Il; Hwang, Kyo Seon; Kwak, Rhokyun; Lee, Jeong Hoon
Abstract : We present a novel ICP preconcentrator that can preconcentrate targets up to 1000-fold with great fabrication flexibility. Abstract : Microfluidic paper-based analytical devices (μPADs) for molecular detection have great potential in the field of point-of-care diagnostics. Currently, a critical problem being faced by μPADs is improving their detection sensitivity. Various preconcentration processes have been developed, but they still have complicated structures and fabrication processes to integrate into μPADs. To address this issue, we have developed a novel paper-based preconcentrator utilizing ion concentration polarization (ICP) with minimal addition on lateral-flow paper. The cation selective membrane ( i.e., Nafion) is patterned on adhesive tape, and this tape is then attached to paper-based channels. When an electric field is applied across the Nafion, ICP is initiated to preconcentrate the biomolecules in the paper channel. Departing from previous paper-based preconcentrators, we maintain steady lateral fluid flow with the separated Nafion layer; as a result, fluorescent dyes and proteins (FITC–albumin and bovine serum albumin) are continuously delivered to the preconcentration zone, achieving high preconcentration performance up to 1000-fold. In addition, we demonstrate that the Nafion-patterned tape can be integrated with various geometries (multiplexed preconcentrator) and platforms (string and polymer microfluidic channel). This work would facilitate integration of various ICP devices, including preconcentrators, pH/concentration modulators, and micro mixers, with steady lateral flows in paper-based platforms.